2014
DOI: 10.7439/ijbr.v5i4.584
|View full text |Cite
|
Sign up to set email alerts
|

Multi-drug Resistant Pseudomonas aeruginosa Isolated from Intensive Care Burn Unit

Abstract: This prospective study was conducted on burn patients visiting Victoria Hospital, Kalasipalayan, Bangalore, India from Nov 15, 2010 to June 15, 2011. A total of 100 samples were collected from the burn patients. Pus sample were collected from wound using a sterile cotton swab and transported to the laboratory using Stuart's medium without delay. Speciemen were inoculated on MacConkey agar, Blood agar and Nutrient agar plates and the plates were incubated at 37°C over night. Initial diagnosis of isolates was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…A study carried out by Upadhyay et al, in 2014 showed that 17% of P. aeruginosa among infected burns patients, which is almost similar to present study (Upadhaya, 2014 Iraj et al, (2013) showed that resistance to Ciprofloxacin was 63.3% and according to Upadhyay et al, resistance to cefepime was 64.7% which is also similar to our study (Upadhaya, 2014;Iraj et al, 2013). Present study shows least resistance against Imipenem (33.3%), Piperacillin/Tazobactum (33.3%), Colistin (16.7%) similar study done by Iraj et al,obtained 23.3% resistance to Imipenem (Iraj et al, 2013) (Fig.…”
Section: Resultssupporting
confidence: 90%
“…A study carried out by Upadhyay et al, in 2014 showed that 17% of P. aeruginosa among infected burns patients, which is almost similar to present study (Upadhaya, 2014 Iraj et al, (2013) showed that resistance to Ciprofloxacin was 63.3% and according to Upadhyay et al, resistance to cefepime was 64.7% which is also similar to our study (Upadhaya, 2014;Iraj et al, 2013). Present study shows least resistance against Imipenem (33.3%), Piperacillin/Tazobactum (33.3%), Colistin (16.7%) similar study done by Iraj et al,obtained 23.3% resistance to Imipenem (Iraj et al, 2013) (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Mozami -Gordarzi and Eftekhar in their study found 94.7% isolates resistant to both imipenem and meropenem. Similarly Upadhaya et al, (2014) showed 94.1% and 88.2% resistance to meropenem and imipenem respectively in their study. …”
Section: Resultsmentioning
confidence: 63%
“…Bhatt et al, (2015) showed 84% and 75% resistance to gentamicin and tobramycin respectively. However Upadhaya et al, (2014) showed 47.1% and 100% isolates to be resistant to gentamicin and tobramycin respectively.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the past few decades, MDRPs increasing worldwide recognized as a pathogens in a variety of serious infections in hospitalized patients. [1][2][3] The carbapenemes have been drug of choice for the treatment of serious infection caused by gram negative bacterial infections. [4] Pseudomonas shows resistance to carbapenem due to decrease outer membrane permeability, increased efflux system, alteration penicillin binding protiens and carbapenem hydrolyzing enzymes carbapenemase.…”
Section: Introductionmentioning
confidence: 99%